ТРИВАЛА ДІЯ ІОНІЗУВАЛЬНОГО ВИПРОМІНЮВАННЯ В НИЗЬКИХ ДОЗАХ ТА ПАНДЕМІЯ COVID-19: ОНКОГЕМАТОЛОГІЧНІ АСПЕКТИ - Gluzman, D.F.; Zavelevich, M.P.; Philchenkov, A.A.; Koval, S.V.; Guslitser, L.N.; Zinchenko, V.N.; Bezhenar, T.O. (PH Akademperiodyka, 2023)
Summary. For more than 35 years after Chornobyl catastrophe, about 5 million people in Ukraine, Republic of Belarus and Russian Federation inhabit the territories that are residually contaminated with long-lived radionuclides such as 137Cs, 90Sr. The previous studies of the Reference Laboratory operating at RE Kavetsky Institute of Experimental Pathology, Oncology and Radiobiology allowed specifying the effects of the protracted low dose irradiation on the state of the hematopoietic and lymphoid tissues resulting in the increased proportion of the B-cell chronic lymphocytic leukemia/small lymphocytic lymphoma and acute myeloid leukemia among the patients referred from the contaminated areas of Ukraine. Since the beginning of 2020, these effects of radiation were superimposed by the factors associated with COVID-19 pandemic. SARS-CoV-2 infection is associated with the significant impact on hematopoiesis and immune system. Particular attention should be given to the role of such combined burden in the development of the immunodeficiency-associated lymphoid neoplasms. The extensive studies of the combined effects of low dose irradiation and COVID-19 within the large affected populations could be made a priority in future endeavors of epidemiologists and oncohematologists.